Larvae, lemures, manes in the Apuleius’s demonology and the popular believes of romans - Hidalgo de la Vega, María José (ARYS. Antigüedad: Religiones y Sociedades, 2020)
This paper treats to analyse the Apuleius’s of Madaura demonologic aspects and the popular and cultured beliefs, showing a symbiosis between magic and religion. This syncretism of the beliefs and sensibilities established the religious and cultural background in the age of the Antonines and the Severians.
Keywords: Roman Empire; Apuleius; demonology; magic and religion